(untitled) (AYUSHDHARA, 2019)
Ancient Surgical science -Shalya tantra embraces all processes aiming at the removal of factors responsible for producing pain or misery to the body or mind. Among all surgical and para surgical procedures, Ksharasutra is one of the most important technique in the management of Bhagandara (Fistula) and Arsas (Hemorrhoids) diseases. Trials were held in renowned medical institutes in various cities of India. The method is fully standardized and is extensively used. In this review an attempt has been made to highlight the whole concepts of Ksharasutra in under following headings, Introduction, definition, historical aspects, Ingredients, method of prepation, Mechanism of action of Ksharasutra, Uses, Advantage, Disadvantage, Different varieties of Ksharasutra.